PENGARUH PENGENAAN PAJAK PERTAMBAHAN NILAI DAN CUKAI ROKOK TERHADAP SKEMA FINANSIAL PRODUK ROKOK - Fadillah, Reza; Kiswara, Endang (Diponegoro Journal of Accounting, 2012)
The aim of this research was to analyze the effect of cigarette excise tax and value added tax of cigarette price per unit, sales revenue, and production volume to tobacco companies listed in the customs office in Surakarta during the years of 2008 and 2009 either wholly or altogether.There were five variables in this research that consist of two independent variables namely excise per unit and value added tax per unit and three dependent variables that are cigarette price per unit, sales revenue, and production volume. Statistical method used in this research is multiple regressions.According to the results of research, it can be concluded that cigarette excise tax per unit and value added tax per unit only have the effect of cigarette price per unit both separately and collectively.